Social protection and foundational cognitive skills during adolescence: evidence from a large public works programme - Freund, R; Favara, M; Porter, C; Behrman, J (Oxford University Press, 2023)
Many low- and middle-income countries have introduced public works programs (PWPs) to fight poverty. This paper provides the first evidence that children from families who benefit from PWPs show increased foundational cognitive skills. The results, based on unique tablet-based data collected as part of a long-standing longitudinal survey, show positive associations between participation in the Productive Safety Net Programme (PSNP) in Ethiopia during childhood with long-term memory and implicit learning, and suggestive evidence for working memory. These associations appear to be strongest for children whose households were still PSNP participants in the year of data collection. Evidence suggests that the association with implicit learning may be operating partially through children's time reallocation away from unpaid labor responsibilities, while the association with long-term memory may in part be due to the program's success in remediating nutritional deficits caused by early-life rainfall shocks.